2002
DOI: 10.1111/j.1945-5100.2002.tb01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Northwest Africa 482: A crystalline impact‐melt breccia from the lunar highlands

Abstract: Abstract-Northwest Africa 482 (NWA 482) is a crystalline impact-melt breccia from the Moon with highlands affinities. The recrystallized matrix and the clast population are both highly anorthositic. Clasts are all related to the ferroan anorthosite suite, and include isolated plagioclase crystals and lithic anorthosites, troctolites, and spinel troctolites. Potassium-, rare-earth-element-, and phosphorus-bearing (KREEP) and mare lithologies are both absent, constraining the source area of this meteorite to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
(32 reference statements)
3
27
0
Order By: Relevance
“…This is due to the lack of a KREEP component in the NWA482 melt and to the fact that it represents a feldspathic melt that was produced by an impact into a much different crustal terrain than the Apollo 14 and 17 melts described above (Korotev et al, 2006). The impact event that generated the impact melt breccia occurred at $3.75 Ga (Daubar et al, 2002). Following that impact event, the rock was shocked in another, less intense impact event.…”
Section: Lunar Meteorite Nwa482mentioning
confidence: 95%
See 1 more Smart Citation
“…This is due to the lack of a KREEP component in the NWA482 melt and to the fact that it represents a feldspathic melt that was produced by an impact into a much different crustal terrain than the Apollo 14 and 17 melts described above (Korotev et al, 2006). The impact event that generated the impact melt breccia occurred at $3.75 Ga (Daubar et al, 2002). Following that impact event, the rock was shocked in another, less intense impact event.…”
Section: Lunar Meteorite Nwa482mentioning
confidence: 95%
“…The complete stone had a mass of about 1 kg and represents 3% of the total mass of known lunar meteorites. It is a very fine-grained crystalline impact melt breccia with highlands affinities (Grossman and Zipfel, 2001;Daubar et al, 2002). The matrix and the clast population are both highly feldspathic (Fig.…”
Section: Lunar Meteorite Nwa482mentioning
confidence: 98%
“…Mare basalts, KREEP, and Mg‐suite lithologies are absent (Daubar et al. ; Korotev et al. ; Warren et al.…”
Section: Lunar Meteoritesmentioning
confidence: 99%
“…The sample was crushed to a grain size <750 µm to obtain average bulk material. We measured two splits of 22.31 mg and 22.80 mg. Daubar et al (2002) concluded that NWA 482 is a crystalline impact melt breccia from the highlands of the Moon, and furthermore, that its short terrestrial age, combined with the unique lithology, preclude any pairing with other NWA lunar meteorites. The chemical composition was measured by .…”
Section: Samples and Experimental Proceduresmentioning
confidence: 99%